2016
DOI: 10.1163/22142312-12340055
|View full text |Cite
|
Sign up to set email alerts
|

Sinophone, Chinese, and prc Internet

Abstract: Recently, while there have been some who advocate the notion of a Sinophone internet, approximately coterminous with a Chinese-literate user base (Sullivan & Chen 2015), others have argued the internet in China should be known as the Chinese internet (Yang 2015: 1). This paper extends from the call to specificity to ask how the suggestion of the Chinese internet might manifest itself and what it might mean for the Chinese overseas. This is specifically in light of the multiplicity and heterogeneity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(5 reference statements)
1
5
0
Order By: Relevance
“…Figure 2 below shows their respective places of origin. The diversity affirms the scholarly observation about the cultural discursiveness of "Chineseness" in Australia (Leong, 2016). Demographic information collected showed that most participants were 60 years or older (Figure 3).…”
Section: Methodology -An Ethnographic Approachsupporting
confidence: 78%
See 1 more Smart Citation
“…Figure 2 below shows their respective places of origin. The diversity affirms the scholarly observation about the cultural discursiveness of "Chineseness" in Australia (Leong, 2016). Demographic information collected showed that most participants were 60 years or older (Figure 3).…”
Section: Methodology -An Ethnographic Approachsupporting
confidence: 78%
“…Empirically, such a community group-orientated structure has played an essential role in shaping the way of life for research participants and how they have obtained ACP and health information in Australia. This observation is particularly important for the Chinese community where the community structure appears to be somewhat fragmented due to the social and cultural discursiveness and fluidity (Leong, 2016). As a social unit, community organizations can offer the conceptual and analytical lens to observe and envisage the way Chinese Australians respond to ACP information.…”
Section: Community Structures and Implicationsmentioning
confidence: 99%
“…We use the term 'home place' to recognise the diversity and plurality of Chineseness within and beyond the mainland PRC region (Leong, 2016). This study uses a combined participant observation and focus groups (eight on-site focus group interviews with 32 ECMs).…”
Section: Dis/trust As the Underlying Principle Of Digitisationmentioning
confidence: 99%
“…Azlan 2020;Beta 2020;Duong 2019;Lengauer 2022;Liew & Abidin 2020;Pan 2017;Sharma 2020; see also Barendregt & Schneider 2020). The same can be said of questions about space (see, in particular, Gairola & Roth 2019), for instance with regard to digital space and heritage (Müller 2019), 'hybrid media' spaces (Postill & Epafras 2018), the connection between digital practices and physical (often urban) space (Ruiz Andrade 2019; Sharma 2022; Sneep 2019; Swaminathan 2015; Wang 2020), and the many different ways in which actors construct and manage 'digital space' , whether through national policy and state control (Leong 2016) or capitalist market dynamics (Roth 2019). These themes are as relevant today as they were then, and several of the contributions to this anniversary issue follow up on these earlier concerns.…”
mentioning
confidence: 99%
“…This is understandable, considering the language barriers and institutional divides within university departments, which are often reproduced in scholarship on digital Asia. In some cases, the nature of the subject may well channel scholars into national contexts, perhaps because a specific nation-state is building a national digital infrastructure, of which China is arguably the most high-profile example (see also Leong 2016). Although this Asiascape: Digital Asia 10 ( 2023) 5-29 focus may be justifiable, especially when scholars are interested in neatly defined cases on platforms that are, at least to some degree, country specific (e.g.…”
mentioning
confidence: 99%